PENGARUH SIMULASI TERHADAP PENINGKATAN PENGETAHUAN DAN KETERAMPILAN APARATUR DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN KABUPATEN SUMBAWA BARAT - JAYADI, MUHAMMAD; ZULKIEFLIMANSYAH, ZULKIEFLIMANSYAH; UMAR, UMAR (GANEC SWARA, 2023)
The number of fire incidents in West Sumbawa Regency has increased significantly. In response to this problem, the study attempted to examine the issue of evaluating the effect of simulation training on improving the knowledge and skills of the Fire Service apparatus of West Sumbawa Regency. This study used a comparative causal research method involving 30 respondents out of 75 total research respondents and used a quantitative approach to measure the impact of simulation training on increasing the knowledge and skills of the apparatus. From the test results obtained, it has a Cronbach alpah value> 0.804 from the R Tabe value of 0.600 so that the instrument can be declared reliable and has a very high influence on increasing the knowledge and skills of the Fire Apparatus. this supports the hypothesis that simulation training has a positive impact on the knowledge and skills of fire fighting apparatus. The implications of this research provide a basis for the West Sumbawa Regency Fire Service to consider the integration of simulation training as an effective strategy in improving the readiness and skills of the apparatus in dealing with fire and other emergency situations.